A1298C Polymorphism of Fetal Methylenetetrahydrofolate Reductase (MTHFR) Gene as a Risk Factor for Spontaneous Abortion - Isah Sulfiana; St Maisuri T Chalid; Retno B Farid; Syahrul Rauf; Eddy Hartono (Indonesian Journal of Obstetrics and Gynecology, 2016)
Objective: To investigate the role of A1298C polymorphism of fetal methylenetetrahydrofolate reductase (MTHFR) gene in spontaneous abortion. Method: The case control study design recruited 96 subjects in Siti Fatimah and Pertiwi mother and child hospital, Dr. Wahidin Sudirohusodo, Pelamonia, Bhayangkara, Syekh Yusuf, Haji and Labuang Baji hospital from March to September 2014. All subjects fulfilling the inclusion criteria were taken tissue samples from mothers experiencing spontaneous abortion and blood samples from normally born baby. The data were analyzed using Pearson chi-square with significant rate of 5% (p